Manufacturing strategy formation process: case study of Iranian manufacturing companies - Ghazinoory, Sepehr; Khotbesara, Rahman Mahdiani; Fardoei, Sedigheh Rezaeian (Technological and Economic Development of Economy, 2011)
This paper describes case study research undertaken in six Iranian manufacturing companies aimed at advancing the understanding of the manufacturing strategy formation process. As shown in this study, culture, leadership, policy and incrementalism have their own undeniable roles in manufacturing strategy formation. Cultural factors impact on political factors, and political factors impact on individual factors. It could be useful To utilize formal business planning for firms interested in deliberative manufacturing strategy. In this study, we use Barnes's manufacturing strategy formation process as frameworks with some new changes. Also a case study methodology was used to investigate the process of formation of manufacturing strategy in six small manufacturing companies in Iran like Barnes did in the UK. The results of this study are the main features of the process of manufacturing strategy formation and manufacturing strategy formation model in the case companies. In the case study method, external validity is inevitably compromised due to the limited number of companies that can be studied. The demonstrated model in this study offers a comprehensible view in organizational and external contexts that can be used by manufacturing decision makers.Article in English.Gamybos strategijos formavimo procesas Irano gamybos įmonėseSantrauka. Straipsnyje aprašomi šešiose Irano gamybos įmonėse atlikti moksliniai tyrimai, įrodantys gamybos strategijos formavimo proceso reikšmę. Tyrimas nustatė, kad kultūra, vadovavimas ir politika turi savo neginčijamą įtaką gamybos strategijos formavimo procese. Kultūriniai veiksniai daro įtaką politiniams veiksniams, o politiniai veiksniai veikia individualius veiksnius. Gali būti naudinga naudoti formalų verslo planavimą formuojant įmonės gamybos strategiją. Šiame tyrime buvo naudojamas modifikuotas Barnes gamybos strategijos formavimo procesas. Barnes pavyzdžiu buvo siekiama ištirti gamybos strategijos formavimo procesą šešiose nedidelėse Irano gamybos įmonėse. Šio tyrimo rezultatai atskleidė tiriamų įmonių gamybos strategijos formavimo proceso ypatumus. Tyrimui neišvengiamo subjektyvumo suteikia ribotas ištirtų įmonių skaičius. Pasiūlytas modelis leidžia visapusiškai ištirti vidinę ir išorinę organizacijos aplinkas bei pasiūlyti sprendimus gamybos planuotojams.Reikšminiai žodžiai: gamybos strategija, strategijos formavimas, apgalvoti sprendimai, staigūs sprendimai, Iranas.First published online 18 Jan 2012